Internalisasi Moderasi Beragama Perspektif Fiqih Kontemporer di Desa Tramok Koko Bangkalan - Sumiyati, Sumiyati; Hamidah, Tutik (YASIN, 2024)
The purpose of writing this article is to find out how to analyze the internalization of religious moderation from a contemporary fiqh perspective and what the implications of religious moderation from a contemporary fiqh perspective are that occur in the village of Tramok Kokop Bangkalan. This method uses a descriptive qualitative approach carried out with data analysis which is used as a process of collecting data, presenting data, drawing conclusions. The type of research in this article uses a case study type by focusing on a problem that you want to know and understand in depth and universally. The results of this research reveal that the internalization of religious moderation from the perspective of contemporary jurisprudence concludes that the process of internalization of religious moderation from the perspective of contemporary jurisprudence is more inclined towards the social attitudes of local communities with various social, religious and customary activities by prioritizing adab rather than ego, both among local communities and outside communities and The implications of religious moderation from contemporary Islamic jurisprudence perspectives that occur in society can build and establish stronger social relations so as to create peaceful, safe, secure and prosperous social life between communities and religion.